2014
DOI: 10.1071/zo13079
|View full text |Cite
|
Sign up to set email alerts
|

Variation in platypus (Ornithorhynchus anatinus) life-history attributes and population trajectories in urban streams

Abstract: An understanding of animal population dynamics relies on identifying life-history attributes associated with population growth and determining how these are affected by environmental variables. We analysed platypus population processes over a 10-year period through mark–recapture studies conducted in three spatially independent stream systems located in the suburbs of Melbourne, Australia. The three populations were collectively characterised by a slightly male-biased adult sex ratio (1.15 : 1) and relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…We illustrate the application of these methods using a case study of a unique Australian freshwater mammal, the platypus ( Ornithorhynchus anatinus ), in Melbourne, Victoria. The platypus has recently been upgraded to ‘Near Threatened’ by the International Union for the Conservation of Nature, due to recent evidence of declines in some areas, and the species’ dependence on adequate water and flows (Grant, ; Serena, Williams, Weeks, & Griffiths, ). Historical platypus surveys have relied on fyke nets for detecting platypus populations, but the species’ cryptic nature means that this sampling method may lack the sensitivity needed to reliably assess the number of occupied sites in any given year, or to detect changes in the number of occupied sites over time (Gust & Griffiths, ; Lunney et al., ; Woinarski, Burbidge, & Harrison, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We illustrate the application of these methods using a case study of a unique Australian freshwater mammal, the platypus ( Ornithorhynchus anatinus ), in Melbourne, Victoria. The platypus has recently been upgraded to ‘Near Threatened’ by the International Union for the Conservation of Nature, due to recent evidence of declines in some areas, and the species’ dependence on adequate water and flows (Grant, ; Serena, Williams, Weeks, & Griffiths, ). Historical platypus surveys have relied on fyke nets for detecting platypus populations, but the species’ cryptic nature means that this sampling method may lack the sensitivity needed to reliably assess the number of occupied sites in any given year, or to detect changes in the number of occupied sites over time (Gust & Griffiths, ; Lunney et al., ; Woinarski, Burbidge, & Harrison, ).…”
Section: Introductionmentioning
confidence: 99%
“…We illustrate the application of these methods using a case study of a unique Australian freshwater mammal, the platypus (Ornithorhynchus anatinus), in Melbourne, Victoria. The platypus has recently been upgraded to 'Near Threatened' by the International Union for the Conservation of Nature, due to recent evidence of declines in some areas, and the species' dependence on adequate water and flows (Grant, 1998;Serena, Williams, Weeks, & Griffiths, 2014).…”
mentioning
confidence: 99%
“…These observations are consistent with an underlying pattern of limited dispersal of (at least some) relatives. This is somewhat surprising given that previous studies using mark-recapture approaches in the Shoalhaven River (Grant, 2004b;Bino and Grant, 2015) and other streams (Serena, 2012;Serena et al, 2014) have reported the dispersal of a high proportion of juveniles, especially males, few recaptures of adult males, and the continued capture of unmarked males and females. Of all the pairs of relatives we sampled at the same site, most were female-female or male-female, and not male-male (there are only three male-male relative pairs in Table S4), which is consistent with male-biased dispersal.…”
Section: Discussionmentioning
confidence: 88%
“…We also examined the maximum total monthly flows between January and December and maximum total monthly flows between January and April, the period aligning with the platypus’ breeding and emergence of young. High stream flows can reduce the availability of macroinvertebrate prey species 24 , increase metabolic demand on foraging platypuses 42 and drown dependent nestlings in burrows during the breeding season 22 24 .…”
Section: Methodsmentioning
confidence: 99%
“…The platypus is “of least concern”, under current IUCN red listing 20 , but were identified recently as ‘near threatened’, given localised declines and extinctions in populations, particularly in the state of Victoria 21 . Despite increasing understanding, many aspects of the species’ biology, including its population dynamics remain relatively poor, reliant on few long-term studies investigating densities, reproduction, age structure and survival 22 23 24 . There are generally low recapture rates 22 25 , making reliable estimates of population sizes difficult.…”
mentioning
confidence: 99%